Perancangan Alat Pendeteksi Kebakaran Dengan Arduino Menggunakan Konsep Internet of Things (IoT) Pada Bengkel D2 Tech - Evan Nurfaizi; Achmad Udin Zailani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Along with the development of technology, especially the Internet of Things (IoT) is currently encouraging people to continue to think creatively to develop systems that can provide security and convenience in carrying out daily activities. By incorporating the Internet of Things (IoT) concept into a tool, it will simplify our activities so that they are more effective (Rizky Abrar, Mariadi Kaharmen, and Nur Hakim 2020). To overcome the problems faced by the D2 Tech workshop in terms of preventing fires due to the large number of items and liquids that are flammable, therefore this study aims to design a tool that can detect, provide fire warning information and handle directly if a fire is detected so that the owner the workshop feels safe about its business. The method used for system development is to use the Prototype method. The prototype method is an initial model of a product designed to test a concept or description of our idea (Darnita, Discrise, and Toyib 2021). Based on the results of the tests that have been carried out, the design of a fire detection tool with Arduino with the internet of things concept can work well and provide the expected results according to its functionality. In conclusion 1. The design of the tool that has been made can be used properly for fire detection and monitoring smoke and room temperature via the Blynk app. 2. The design of this tool that has been built can extinguish the fire directly when a fire is detected. 3. The design of the tool that has been made can turn on the installed alarm and send notifications to Telegram.